2017
DOI: 10.1200/jco.2016.70.4627
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of BRCA1/2 Germline Mutations Detected in Circulating Tumor DNA From Patients With High-Grade Serous Ovarian Cancer

Abstract: Purpose Germline BRCA1 or BRCA2 mutations in patients with high-grade serous ovarian cancer (HGSC) are associated with favorable responses to chemotherapy. However, secondary intragenic (reversion) mutations that restore protein function lead to clinically significant rates of acquired resistance. The goal of this study was to determine whether reversion mutations could be found in an unbiased manner in circulating cell-free DNA (cfDNA) to predict treatment response in HGSC. Patients and Methods Plasma and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 20 publications
1
118
0
Order By: Relevance
“…We first established the potential of the assay for detecting ctDNA in patients with ovarian cancer, as prior studies suggested low rates of mutation detection in ctDNA of ovarian cancer patients (46). Massively parallel sequencing analysis of germline DNA from peripheral blood leukocytes, microdissected tumor and plasma DNA of 19 cases ( BRCA1 , n=12; BRCA2 , n=7), using previously validated methods (18,20), yielded median depths of coverage of 1,569x (range 852x–2,272x), 823x (range 272x–2,328x) and 1,978x (range 1,287x––4,157x), respectively (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first established the potential of the assay for detecting ctDNA in patients with ovarian cancer, as prior studies suggested low rates of mutation detection in ctDNA of ovarian cancer patients (46). Massively parallel sequencing analysis of germline DNA from peripheral blood leukocytes, microdissected tumor and plasma DNA of 19 cases ( BRCA1 , n=12; BRCA2 , n=7), using previously validated methods (18,20), yielded median depths of coverage of 1,569x (range 852x–2,272x), 823x (range 272x–2,328x) and 1,978x (range 1,287x––4,157x), respectively (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…BRCA1 and BRCA2 reversion mutations have been documented as potential mechanisms of resistance to platinum-based chemotherapy and PARP inhibitors in cell line models and patient samples (4,13,14,21,46). Here we report on the detection of putative BRCA1 and BRCA2 reversion somatic mutations in the cfDNA of platinum-based chemotherapy and/or PARP inhibitor resistant/ refractory ovarian and breast cancer patients harboring germline BRCA1 or BRCA2 germline mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In both high-grade serous ovarian cancer and metastatic prostate cancer, multiple secondary mutations in both germ-line and somatically mutated BRCA2 and PALB2 were identified in cfDNA from patients with recurrent disease (Christie et al 2017, Goodall et al 2017, Quigley et al 2017). Interestingly, in the case of prostate cancers treated with PARPi (either olaparib or talazoparib), analysis of mutations in cfDNA revealed evidence of multiclonal heterogeneity of BRCA2 reversion mutations, information that would be difficult to glean from a single tumor biopsy sample (Quigley et al 2017).…”
Section: Mechanisms Of Resistance To Poly(adp-ribose) Polymerase Imentioning
confidence: 99%
“…Multiple mechanisms of resistance to PARPi have been proposed (reviewed in [11]). Amongst these, secondary reversion mutations in the BRCA1/2 genes have been associated with clinical resistance to platinum or olaparib (1214). However, the mechanism of resistance in prostate cancer, and to PARPi other than olaparib, is unknown.…”
Section: Introductionmentioning
confidence: 99%